2020
DOI: 10.1007/s13205-020-02476-y
|View full text |Cite
|
Sign up to set email alerts
|

Induction of esterase activity during the degradation of high concentrations of the contaminant di(2-ethylhexyl) phthalate by Fusarium culmorum under liquid fermentation conditions

Abstract: In this study, the induction of esterase activity during the degradation of a high concentration of di(2-ethylhexyl) phthalate (DEHP) (1500 mg l −1 ) by Fusarium culmorum was investigated using Ca(NO 3 ) 2 as nitrogen source under liquid fermentation conditions. Assessments of esterase activities through biochemical tests and zymographic assays, as well as fungal growth were studied. A high concentration of DEHP increased esterase activity in F. culmorum, which produces five esterase isoforms (26.4, 31.7, 43, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…These microorganisms may enhance pollutant degradation in phthalate-contaminated environments. Several investigations have revealed that fungal species such as Polyporus brumalis , Ganoderma lucidum , Trametes versicolor , Phlebia tremellosa , Neurospora sithopila , P. ostreatus , Phoma sp., Stropharia rugosoannulata , Ascocoryn e sp., Puccinia arenariae are phthalate-degrading organisms (Hwang et al, 2008 ; Kim et al, 2008 ; Lee et al, 2007 ; Kim & Song, 2009 ; Ahuactzin-Pérez et al., 2018a , 2018b ; Carstens et al, 2020 ; González-Márquez et al, 2019 ; González-Márquez et al, 2020 ; Hwang et al, 2012 ; Liao et al, 2012 ; Luo et al, 2012 ; Sánchez, 2021 ; Sánchez-Sánchez & Sánchez, 2019 ). In particular, fungi such as Fusarium species have been reported to degrade phthalates due to their esterase production.…”
Section: Introductionmentioning
confidence: 99%
“…These microorganisms may enhance pollutant degradation in phthalate-contaminated environments. Several investigations have revealed that fungal species such as Polyporus brumalis , Ganoderma lucidum , Trametes versicolor , Phlebia tremellosa , Neurospora sithopila , P. ostreatus , Phoma sp., Stropharia rugosoannulata , Ascocoryn e sp., Puccinia arenariae are phthalate-degrading organisms (Hwang et al, 2008 ; Kim et al, 2008 ; Lee et al, 2007 ; Kim & Song, 2009 ; Ahuactzin-Pérez et al., 2018a , 2018b ; Carstens et al, 2020 ; González-Márquez et al, 2019 ; González-Márquez et al, 2020 ; Hwang et al, 2012 ; Liao et al, 2012 ; Luo et al, 2012 ; Sánchez, 2021 ; Sánchez-Sánchez & Sánchez, 2019 ). In particular, fungi such as Fusarium species have been reported to degrade phthalates due to their esterase production.…”
Section: Introductionmentioning
confidence: 99%
“…The pH value in the cultures is an indicator of the substrate degradation process. Acid molecules were released into the media during the first 24 h of fermentation, decreasing the pH value, whereas amino compounds were formed after 32 h, which increased the pH value (González-Márquez et al 2020;González-Márquez and Sánchez 2022). Gonzalez-Márquez et al (2019a) studied the growth of the fungus F. culmorum using different apple cutin concentrations (0.2, 2, and 20 g/L) under submerged fermentation conditions and found that the pH of the cultures increased from the initial pH 6.5 to pH 7.5 after 168 h. The pH variation of the fungal cultures depends on the substrate composition and fermentation system.…”
Section: Time Of Fermentation (H)mentioning
confidence: 99%
“…The production of cutinases is regulated by microbial growth conditions, carbon source, and fermentation system (Liang and Zou 2023). The enzymatic activity of cutinases is induced by the presence of cutin and cutin monomers in the culture medium (Degani 2015;González-Márquez et al 2019a;González-Márquez and Sánchez 2022). Cutin is the main component of the plant cell wall.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Trichoderma harzianum has been described to be able to degrade the plasticizer di(2-ethyl hexyl) phthalate, which make plastics elastic, flexible and extensible (Aguilar-Alvarado et al, 2015). Some ascomycete fungi have been reported to be highly efficient phthalate-degrading organisms due to their secretion of enzymes such as esterase (Chhaya & Gupte, 2013;Aguilar-Alvarado et al, 2015;Bouchiat et al, 2015;Ahuactzin-Pérez, et al, 2016;Ferrer-Parra et al, 2018;González-Márquez et al, 2019a,b;Rios-González et al, 2019;González-Márquez et al, 2020;González-Márquez et al, 2021). The addition of surfactants in the medium is a common practice since it makes hydrophobic substrates available to the microorganism.…”
Section: Introductionmentioning
confidence: 99%